Analysis of Mercury (Hg) Distribution In The Waeapo River Irrigation Area, Buru Regency, Maluku Province, Gold Mining Without Permission Result In Botak Mountain Area - Salatutin, Febrian M.; Batawi, Chudeya Y.; Lessil, Camellia Y.; Male, Yusthinus T (Indonesian Journal of Chemical Research, 2015)
The Waeapo River has 13 watersheds, which are irrigated area for thousand hectare of rice field in the District of Buru. Buru District is one of the area that can supply thousands of tons of rice. But, yields to be reduced by the presence of gold mining activities in the Botak Mountain. Gold mining activities not only impact for the decline in yields, but also impact on the quality of rice by mercury pollution generated by mining waste. This research aims to determine the accumulation of mercury in sediment of Waeapo river. The research method is used survey and analysis method. In this research, observations were done and field sampling with the laboratory analyze. The result showed that concentration of analyzed mercury at four point, one point has exceeded standard of mercury limits in the sediment, i.e 0.1 ppm